Implementasi Teknologi Pembelajaran di Perguruan Tinggi Vokasi Indonesia - Masita, Maya; Rossydi, Ahmad (Politeknik Penerbangan Makassar, 2021)
The development of technology, especially in learning, became an issue discussed in recent years. The main benefits of using technology include increasing students' interest and participation in the learning process. Learning technology is a tool used in the learning process to achieve learning objectives. This study is a case study that aims to explore the teaching English by using learning technology such as YouTube, Plickers, and Zoom Meeting at the Indonesian Vocational Higher Education. There were one instructor and sixteen cadets involved in the study. The data was taken using purposive sampling techniques, where the subjects of this study were instructor and cadets who used learning applications. The data are collected by interview and observation and analyzed using interactive model data analysis. This study shows that: 1) the use of learning technology makes cadets more active, 2) cadets are not familiar with learning applications, 3) internet connection is unstable, so the instructors have to prepare another activity. The selection of learning applications that suit cadets' needs make teaching and learning activities more variable.